Dietary Inflammatory Index of Obese Individuals with Obstructive Sleep Apnea: A Descriptive Study - Sousa, Bianca Aparecida de; Vicente, Beatriz Martins; Bastos, Amália Almeida; Ribeiro, Sandra Maria Lima; Aquino, Rita de Cássia de; Quaresma, Marcus Vinícius dos Santos; Tufik, Sergio; De-Mello, Marco Túlio; Melo, Camila Maria de (Sleep Science, 2024)
The objective of the present study was to describe the dietary inflammatory profile and its correlations with sleep parameters of obese individuals with obstructive sleep apnea (OSA). Forty individuals underwent nocturnal polysomnography, anthropometric measurements, body composition by plethysmography, assessment of food consumption by three-day food records, and blood collection for the lipid, glycemic and hormonal profile. Food consumption data were evaluated semiquantitatively, quantitalively assessment, and calculation of the dietary inflammatory index (DII) was perfomed. The results demonstrated a predominantly proinflammatory dietary profile. The participants showed a low intake of fruit and vegetables. Additionally, a low consumption of fiber, magnesium, vitamin D, and vitamin E was observed, although there was an adequate distribution of macronutrients. In conclusion, although the inflammatory profile did not correlate with OSA, the study showed a directly proportional relationship between adequate dietary patterns and better sleep quality.
Keywords: obstructive sleep apnea; dietary inflammatory index; dietary patterns; sleep